Impact of Multimedia on Teaching - Learning Process at Public Sector Primary Schools (grade 5th) in Quetta, Balochistan - Alia Ayub; Abdul-Nasir Kiazai (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2021)
Purpose: This era is the era of technology, rapid increase in the knowledge needs technology for its effective communication. This research focused on the use of multimedia and its impact on teaching-learning process. Methodology: The pre-test and post-test experimental design was used in this study.  The results of the screening tests and the test scores of the assessed and investigated class were verified to determine the learning outcomes reached between the two groups. Sample of the study was 200. 100 male and 100 female students from 5th grade were selected as sample of this study. Multimedia was used in Pakistan Studies' teaching. Different difficult topics e.g. map, rivers and their locations, land and its types, etc. were taught by the use of multimedia, which supports the videos and graphical colorful images. The data was analyzed by using statistical package, paired sample t-test. Findings: The results highlights the use of multimedia as powerful agent in enhancing the teaching-learning process and motivating the students towards learning. Implication: Policy makers should emphsized on usage of  multimedia in Govt. primary schools. Its a technology should be used as essential part of the teaching as It make the learning not only joyful but also provide in-depth understandings of the difficult concepts.